Subsistence Farming's Contribution to Food Security in South Africa (International Journal of Innovative Research in Computer Science & Technology, 2022)
Food is obtained by poor families via the Markets, poverty agriculture, and governmental or various  family subsidies are all options. Village people used to  grow most of their own their, but current research show  that even city and rural families are increasingly dependent  on marketplace expenditures, with marketplace buying  accounted for up to 90% of meal supplies in certain cases.  Food costs may represent for as high as 60–80 %  household income in certain parts of Sub-Saharan Africa,  especially for low-income households. Sustenance  farming has the ability to alleviate food insecurity in rural  and urban regions, enhance livelihoods, and help temper  high feed price inflation. To ensure long-term food  security, subsistence/smallholder agriculture production  must be significantly boosted. This may be done by  pushing farmers to pursue long-term production  improvement via the use of higher-quality inputs. This  would necessitate a substantial rise in the usages of  fertilizer, natural inputs, and preservation assets, as well as  the establishment of well inlet and outlet markets to help  farmers acquire and use enhanced input data, industry  one‘s (surplus) output, and reduce contract costs and risks.  Increased output, as well as the intensification of farmed  land, will relieve pressure on crop-sensitive peripheral  regions. Here is a necessity to find out how to discover  cost-effective ways to enhance accessibility to supplies by,  for illustration, boosting delivery and assisting farmers in  generating money so that they can purchase supplies and  engage in infrastructures, so improving food security.
Keywords: Agrarianization; Security; Subsistence; Farming; Urbanization